ACCESS TO AND UTILISATION OF LIBRARY MEDIA RESOURCES AS CORRELATES OF PRISON INMATES’ ACADEMIC PERFORMANCE IN PRIVATE SENIOR SCHOOL CERTIFICATE EXAMINATION IN NIGERIA (2016)
The performance of candidates in the Senior Secondary School Certificate Examination (SSSCE) normally generates negative public comments because of their below average results. Part of these results include those of Nigerian Prison inmates. The Nigerian Prisons Service (NPS) prepares inmates for SSSCE; however, very little is known about the inmates‘ performances, probably because of their confinement. Literature largely dwelt on the academic performance of regular students with little attention to the factors affecting academic performance of prison inmates in Nigeria. This study, therefore, examined access to and utilisation of library media resources as correlates of prison inmates‘ academic performance in private SSSCE organised by West African Examinations Council in Nigeria from 2009-2013. ` The study adopted survey design of the correlational type and the Sense Making, Information Richness and Mastery Learning theories provided the framework. Three prisons viz: Abakaliki (Ebonyi State), Ikoyi (Lagos State) and Kuje Medium Security (Abuja) were purposively selected. Total enumeration method was used to draw 438 inmates who registered for SSSCE between 2009 and 2013. The choice of subjects was based solely on eleven social sciences and humanities that require no laboratory facilities. The subjects were: English Language, Mathematics, Further Mathematics, English Literature, Economics, Government, Geography, Commerce, Accounting, Christian Religious Studies and Islamic Religious Studies. The three instruments used were: Inmates‘ Accessibility to library media resources (r=0.72), Utilisation of library media resources (r=0.82) and the SSSCE results collected from the NPS authority. These instruments were complemented with an interview schedule. Data were analysed using Pearson product moment correlation and Multiple regression at 0.05 level of significance. The interview schedule transcripts were content analysed. Access to and utilisation of library media resources significantly contributed to the academic performance of prison inmates (F (1, 435) = 108.87) and jointly accounted for 33.4% of the total variance of the dependent variable. There were significant relative contributions of accessibility of resources (β = .38, t = 3.76) and utilisation of resources (β = .20, t = 1.99) to academic performance of the respondents. Positive significant relationships were established between accessibility to library media resources (r = .57); Utilisation of library media resources (r = .56) and academic performance of inmates in Nigerian prisons. The prison inmates noted that Oxford English Dictionary and textbooks in the 11 subjects were the most accessible and well utilised by them. None of the prison libraries open at weekend while Abakaliki and Kuje prisons had no photocopying facilities. Access to and utilisation of library media resources had a positive relationship on the academic performance of inmates in Nigerian prisons. Increased access to and utilisation of library media resources by prison inmates to improve their academic performance in senior secondary school certificate examination in Nigeria should be considered. Keywords: Access to and utilisation of library media resources, Academic performance of prison inmates, Private senior secondary school examination. Word count: 470